Carbon nanotubes as potential candidate for separation of H2CO2 gas pairs. (7th December 2017) - Swain, Suchhanda S.; Unnikrishnan, Lakshmi; Mohanty, Smita; Nayak, Sanjay K.
Abstract: Membrane separation of H2 CO2 gaseous mixtures has been a topic of great interest to the scientific community since these two gases play a crucial role as fuel sources. Numerous significant research has been undertaken to separate these mixtures, but the potentiality of carbon nanotubes (CNT) displays a promise that can be revolutionized. However, the technological challenges like uniform dispersion, optimum quantity for desired performance, still needs to be addressed in achieving optimum performance. This review presents a detailed description about the hurdles in achieving superior separation performance for this H2 CO2 gas pair. Additionally, CNTs based MMMs, which has been recognized as the potential solution has comprehensively discussed along with different strategies to improve the separation performance. It is believed that the present review will provide guidelines for future development of high performance CNT-based MMMs with the potential to accomplish simultaneously better separation efficiency and higher permeability rate. Graphical abstract: Highlights: Separation and purification of H2 and CO2 . Dexterity of Mixed matrix membranes (MMMs) for selective separation. Contradictory rationales behind poor perm-selectivity of H2 and CO2 separation. Potentials of CNTs-based MMMs. Strategies for development of high performance CNTs-MMMs.